The Interactive Effect of SIRT1 Promoter Region Polymorphism on Type 2 Diabetes Susceptibility in the North Indian Population - Rai, Ekta (Public Library of Science, 2012)
Our previous studies have implicated genes mainly involved in the activity of pancreatic β cells in type 2 diabetes (T2D) susceptibility in the North Indian population. Recent literature on the role of SIRT1 as a potential master switch modulating insulin secretion and regulating gene expression in pancreatic β cells has warranted an evaluation of SIRT1 promoter region polymorphisms in the North Indian population, which is the main focus of the present study. 1542 samples (692 T2D patients and 850 controls) were sequenced for the 1.46 kb region upstream the translation start site of the SIRT1 gene. We performed a functional characterization of the SIRT1 promoter region polymorphisms using luciferase assay and observed a single-nucleotide polymorphism (SNP), rs12778366, in association with SIRT1 expression. We propose that TT, the high-expressing genotype of SNP rs12778366 in the SIRT1 promoter region and present in >80% of the North Indian population, was favored under conditions of feast-famine cycles in evolution, which has turned out to be a cause of concern in the present sedentary lifestyle under ad libitum conditions. Case-control association analysis did not implicate rs12778366 in T2DM per se in the studied population. However, our earlier reported risk genotype combinations of mt-ND3, PGC1α, and UCP2-866, when compared with the protective genotype combinations, in the background of the high-expressing TT genotype of SIRT1 SNP rs12778366, showed a very high additive risk [corrected odd ratio (OR) = 8.91; p = 6.5×10(−11)]. The risk level was considerably low in the genotype backgrounds of TX (OR = 6.68; p = 2.71×10(−12)) and CX (OR = 3.74; p = 4.0×10(−3)). In addition, we screened other reported T2D-associated polymorphisms: PIK3R1 rs3730089, IRS1 rs1801278, and PPP1R3 rs1799999, which did not show any significant association in North Indian population. The present paper emphasizes the importance of gene interactions in the biological pathways of T2D, a complex lifestyle disease.